Phytotoxicity associated to microcystins: a review - Bittencourt-Oliveira, M. C. [UNESP]; Hereman, T. C. [UNESP]; Cordeiro-Araujo, M. K.; Macedo-Silva, I [UNESP]; Dias, C. T.; Sasaki, F. F. C.; Moura, A. N. (Int Inst Ecology, 2014)
Microcystins (MC) are the most studied toxins of cyanobacteria since they are widely distributed and account for several cases of human and animal poisoning, being potent inhibitors of the serine/threonine protein phosphatases 1 (PP1) and 2A (PP2A). The phosphatases PP1 and PP2A are also present in plants, which may also suffer adverse effects due to the inhibition of these enzymes. In aquatic plants, biomass reduction is usually observed after absorption of cyanotoxins, which can bioaccumulate in its tissues. In terrestrial plants, the effects caused by microcystins vary from inhibition to stimulation as the individuals develop from seedling to adult, and include reduction of protein phosphatases 1 and 2A, oxidative stress, decreased photosynthetic activity and even cell apoptosis, as well as bioaccumulation in plant tissues. Thus, the irrigation of crop plants by water contaminated with microcystins is not only an economic problem but becomes a public health issue because of the possibility of food contamination, and this route of exposure requires careful monitoring by the responsible authorities.
Fitotocixidade associada às microcistinas: uma revisão
Keywords: Bioaccumulation; Microcystins effects; Crop plants; Aquatic plants; Bioacumulação; Efeitos de microcistinas; Plantas da agricultura; Plantas aquáticas